Mouse monocytes express CD127 by immune cells, not LPS - Yazdani, Reza; Askari, Mozhde; Ahmadi, Amir Moghadam; Azizi, Gholamreza; Ciric, Bogoljub; Boehm, Alexandra; Zhang, Guang-Xian; Rostami, Abdolmohamad (Frontiers in Immunology, 2024)
The essential role of interleukin 7 (IL-7) signaling via its receptor (IL-7R; CD127) in T cell development and function has been well documented. However, CD127 expression and function in myeloid cells, including monocytes, are less clear, especially in mice. In the present study we report an inducible CD127 expression in mouse monocytes/macrophages. This induction is dependent on the presence of other immune cells, highlighting that regulation of CD127 expression on monocytes differs in mice and humans. We demonstrate that CD127 is functional, as IL-7 downregulated its expression. We also saw decreased CD127 expression during inflammation in vivo.Overall, upregulation of CD127 expression in vitro and its downregulation in vivo confirm that CD127 is an inducible marker on mouse monocyte/macrophage cells, in contrast to findings recently published by others. Characterizing the role of CD127 signaling in myeloid cells in inflammatory disorders would be worthwhile in future study.